Capital Structure and Firm Value in Consumer Cyclicals: The Weakening Moderating Role of Profitability During Market Volatility 2021-2024 - Fatimah; Naelati Tubastuvi; Erna Handayani; Meydy Fauziridwan (Politeknik Ganesha Medan, 2026)
This study examines the influence of capital structure, investment decisions, and firm size on firm value, with profitability as a moderating variable. The novelty of this research lies in demonstrating that profitability weakens the relationship between capital structure and firm value, a finding that contrasts with most prior studies, and in employing a Fixed Effect Model (FEM) with Driscoll–Kraay standard errors to address heteroskedasticity. The sample consists of 38 firms selected from 163 consumer cyclical companies listed on the Indonesia Stock Exchange during 2021–2024, resulting in 152 firm year observations. The FEM Driscoll–Kraay results show that capital structure has a positive and significant effect on firm value, indicating that higher leverage can increase market confidence and enhance firm valuation. However, the moderation test reveals that profitability significantly weakens the effect of capital structure on firm value, meaning that when profitability increases, the contribution of leverage to firm value becomes less influential. Meanwhile, investment decisions and firm size do not significantly affect firm value, nor are their relationships moderated by profitability. These findings imply that managers must adjust leverage policies carefully during periods of high profitability, as its value-enhancing impact diminishes, while investors should prioritize analyzing capital structure and profitability as key indicators of firm strength.